Image guidance procedures in radiotherapy for prostate cancer and the influence of body mass index. Issue 4 (23rd April 2014) - Piotrowski, Tomasz; Kaczmarek, Krzysztof; Jodda, Agata; Ryczkowski, Adam; Bajon, Tomasz; Rodrigues, George; Yartsev, Slav
Abstract: Purpose: To investigate possible optimisation of the image guidance procedure for the prostate cancer patients with respect to imaging frequency and patient body mass index (BMI). Methods: The 6, 085 setup correction shifts and BMI for 216 prostate cancer patients treated on tomotherapy units in two centres were analysed. Margins needed to account for inter-fraction target motion with daily only automatic correction and with automatic and manual corrections during one, three or five first fractions as a reference for further treatment without imaging were calculated. Results: The planning target volume margin calculated for the daily automatic correction only scheme was significantly lower than the margins calculated for the image guidance limited to a few initial fractions. Manual corrections after automatic fusion were more important for patients with higher BMI. On average, the patients with normal BMI had manual correction shift of 0·7 mm in anterioposterior direction, while overweight and obese patients required, correspondingly, the shifts of 1·3 and 1·4 mm. Conclusion: Overweight and obese patients require daily imaging with time saving available by performing automatic kV/MV computed tomography registration only. The patients with normal BMI may be treated with imaging guidance during a few initial treatment fractions.